Entropy production analysis of a radial inflow turbine with variable inlet guide vane for ORC application. (15th February 2023) - Wang, Zhiqi; Xie, Baoqi; Xia, Xiaoxia; Luo, Lan; Yang, Huya; Li, Xin
Abstract: The fluctuation of heat source conditions leads to the off-design operation and efficiency reduction of the radial inflow turbine (RIT). The adjustment of the outlet angle of inlet guide vane (IGV) is an important way to improve the turbine performance under off-design conditions. Since the energy dissipation caused by friction and flow separation is the main reason for the reduction of RIT efficiency, the entropy production analysis method is used to diagnose the location with high local energy loss in the RIT and evaluate its total energy loss under different working conditions in this paper. Firstly, an appropriate outlet angle of the IGV is determined according to the inlet pressure and outlet pressure of the RIT in organic Rankine cycle (ORC). Then, the effects of inlet pressure and outlet pressure on its energy loss are studied. The results indicate that the average entropy production rate (EPR) of the rotor in the RIT is the highest, which is mainly from the tip clearance and the inlet region. More than 70% of total entropy production of the turbine comes from the rotor, followed by the diffuser. The turbine can achieve lower total entropy production at higher outlet pressure or lower inlet pressure. Compared with a fixed IGV, the turbine with variable IGV can achieve higher turbine efficiency and output power under off-design conditions. The maximum increase in the efficiency and output power of the turbine with variable IGV under different inlet pressures is 3.8% and 12.9%, respectively. Highlights: Entropy production method is used to evaluate flow loss of radial turbine. Effects of turbine inlet pressure and outlet pressure on entropy production are analyzed. The rotor has the highest total entropy production, followed by the diffuser. Turbine with variable guide vane can achieve better performance than fixed vanes.